Games ancient and oriental and how to play them. [...] the oriental games of Chess, Draughts, Backgammon and Magis squares [...] (Longmanns, Green a. C., 1892)
Die Seiten 116-231 enthalten Schach
st. zas. Os.
Keywords: szachy